Comparison of Disease Characteristics, Organ Damage, and Survival in Patients with Juvenile-onset and Adult-onset Systemic Lupus Erythematosus in a Combined Cohort from 2 Tertiary Centers in Turkey - Artim-Esen, Bahar; Sahin, Sezgin; Cene, Erhan; Sahinkaya, Yasemin; Barut, Kenan; Adrovic, Amra; Ozluk, Yasemin; Kilicaslan, Isin; Omma, Ahmet; Gul, Ahmet; Ocal, Lale; Kasapcopur, Ozgur; et al. (J RHEUMATOL PUBL CO, 2017)
Objective. Age at onset has been shown to affect the clinical course and outcome of systemic lupus erythematosus (SLE). Herein, we aimed to define the differences in clinical characteristics, organ damage, and survival between patients with juvenile-onset (jSLE) and adult-onset SLE (aSLE). Methods. For the study, 719 patients (76.9%) with aSLE and 216 (23.1%) with jSLE were examined. Comparisons between the groups were made for demographic characteristics, clinical features, autoantibody profiles, damage, and survival rates. Results. These results were significantly more frequent in jSLE: photosensitivity, malar rash, oral ulcers, renal involvement, neuropsychiatric (NP) manifestations, and autoimmune hemolytic anemia (AIHA). Of the autoantibodies, a higher frequency of anti-dsDNA and anticardiolipin IgG and IgM were observed in the jSLE group. A significant proportion of patients with aSLE had anti-Sm positivity and pleuritis. The proportion of patients with jSLE who developed organ damage was comparable to that of patients with aSLE (53% vs 47%) and the mean damage scores were similar in both groups. Renal damage was significantly more frequent in jSLE while musculoskeletal and cardiovascular system damage and diabetes mellitus were more prominent in aSLE. Comparison of survival rates of the 2 groups did not reveal any significant differences. Conclusion. We report a higher frequency in the jSLE group of renal involvement, cutaneous symptoms, oral ulcers, NP manifestations, AIHA, and anti-dsDNA positivity. A significant proportion of patients in the jSLE group had damage, most prominently in the renal domain. Our findings might support different genetic/environmental backgrounds for these 2 subgroups.
Keywords: SYSTEMIC LUPUS ERYTHEMATOSUS; JUVENILE; ADULT; DAMAGE; SURVIVAL; 3 ETHNIC-GROUPS; CHILDHOOD-ONSET; HEMOLYTIC-ANEMIA; MULTIETHNIC COHORT; INDEX; NEPHRITIS; FEATURES; CLASSIFICATION; SIMILARITIES; METAANALYSIS; Rheumatology